Targeting soluble guanylate cyclase with Riociguat has potency to alleviate testicular ischaemia reperfusion injury via regulating various cellular pathways - YÜKSEL, MERAL (My University, 2022)
© 2022 Wiley-VCH GmbH.Testicular ischaemia reperfusion (I/R) injury results with serious dysfunctions in testis. This study aims to explore effects of soluble guanylate cyclase (sGC) stimulator Riociguat on experimental testicular I/R injury in rats. Twenty-one male rats were divided into three groups (Control, IR and IRR). The control group was not exposed to any application. Bilateral testis from IR and IRR animals were rotated 720° in opposite directions for 3 h to induce experimental testicular ischaemia. Animals in IR and IRR groups were subjected to 3 h of reperfusion. Isotonic and Riociguat were administered to the animals 30 min prior reperfusion by oral gavage. At the end of experiment, animals were sacrificed and tissue samples were used for analyses. Riociguat treatment significantly decreased tissue malondialdehyde and Luminol levels compared to the IR group (p < 0.05). The pathological changes, pro-apoptotic proteins (Bax, Caspase 3, and Caspase 9) and apoptotic index in the IR group were down regulated in Riociguat treated animals (p < 0.05). Riociguat treatment was also significantly increased anti-apoptotic Bcl-2 expression, but alleviated tissue injury via modulating pro-inflammatory cytokine IL-1β levels and significantly (p < 0.05) down-regulating NF-κB activity. Moreover, mTOR and ERK phosphorylation increased in IR group (p < 0.05), but Riociguat treatment reduced protein phosphorylation. Our experiment indicated that targeting sGC might support surgical interventions in testicular I/R injury by modulating oxidative stress, inflammation, and apoptotic protein expression levels, but more detailed studies are required to explore the protective activity of Riociguat and underlying mechanisms in testicular I/R injury.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; ENDOKRİNOLOJİ VE METABOLİZMA; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; ENDOCRINOLOGY & METABOLISM; Endokrinoloji; Yaşam Bilimleri; Üroloji; Endocrinology; Life Sciences; Urology; ischaemia reperfusion injury; rat; Riociguat; sGC stimulator; testis; TORSION/DETORSION-INDUCED ISCHEMIA/REPERFUSION; OXIDATIVE STRESS; TESTIS ISCHEMIA; DAMAGE; APOPTOSIS; RAPAMYCIN; DURATION; SYMPTOMS; PROTECTS; SALVAGE